MARGARET FULLER’S PUBLICISTIC DIALOGUE WITH AMERICA’S PURITAN HERITAGE - M. P. Kizima (Концепт: философия, религия, культура, 2019)
The article analyzes the work of Margaret Fuller (1810 – 1850), a key figure of American Transcendentalism; it focuses on Fuller’s writings from the New-York Tribune in 1844 – 1846 and their religious dimension. Methodologically the article is based on a close reading of Fuller’s writings and their analysis in the cultural and historical context. Fuller’s works are divided into three groups. The first group is writings covering events in the religious life of the community. The second group is essays on social problems: Fuller here is both a journalist and a social reformer; she writes on slavery, poverty, homelessness, she informs the public and calls for action.Significantly, these essays are rich in religious allusions involving the old Puritan heritage in the urgent public debate. The third group isworks written in the form of sermons: Fuller demonstrates that she was a good preacher, as well as a journalist. It is shown that Fuller was immersed in the religious controversies of her time, but was free of religious prejudice; affirming the spirit of Christianity, she often went beyond denominational boundaries; her main accents were on the ethical and social aspects of religious faith and practices. Fuller criticized the New England Puritans; nevertheless, she regarded Puritanism as a source of American identity, the “noble” blood that could play an important role at the time when the country faced new waves of immigration.The analysis leads to the general conclusion that Fuller’s worksas a publicist werea landmark in the history of American Transcendentalism as it moved beyond the boundaries of New England to encompass the emerging American nation in the international world.